Use and constraints on the use of inland valley ecosystems in central Benin: Results from an inland valley survey - Giertz, Simone; Steup, Gero; Schönbrondt, Sarah (ERDKUNDE, 2012)
This paper assesses the current use and constraints on the use of inland valleys in central Benin are assessed to analyse their agro-potential. The methodology applied in this study is comprised of a survey of local authorities and inland valley users conducted with standardised questionnaires and the mapping of inland valley surfaces with GPS. The questionnaire contains questions to socio-economic aspects such as access to an inland valley, land tenure, current use, use constraints as well as questions to physical properties such as soil quality. In addition to the assessment of the inland valley surface area, this approach enabled a detailed socio-economic and rough physical characterization of all detected inland valleys. In total, 817 inland valleys were surveyed in this study. The local population currently uses sixty-seven percent of the valleys, primarily for crop cultivation. In most cases, only a small part of each surveyed inland valley is used. The intensity of exploitation varies across communes and across seasons. Especially in the more densely populated communes of Djougou and Parakou, where the upland soils are often degraded and arable land has become scarce in recent years, the use of inland valleys is greater than in less populated communes. This exploitation occurs primarily during the rainy season, and only a few farmers cultivate crops during the dry season. This study revealed high unused agro-potential in the inland valleys of central Benin. The main reason why inland valleys in the study area currently remain unexploited is a lack of experience in cultivating wetland. In fact, for more than 60% of the unused inland valleys, the local farmers claim to have no knowledge of which crops are adapted to seasonally waterlogged and swampy land or how to cultivate such crops. Due to climate change and population growth, the agricultural use of inland valleys in this region could become more important in the future. To ensure effective use, farmers should be supported by the regional agricultural organisation CeRPA (Centres Régionaux pour la Promotion Agricol) or development organisations to improve the knowledge of cultivation methods and inland valley management.